Cultural Altruism in Action: Empathy and Collectivism as Predictors of Volunteerism in Indonesian Disaster Response - Putrawansyah (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
This study investigates how empathy and collectivism influence volunteerism in Indonesia’s disaster response contexts. Framed within a culturally embedded model of altruism, the research employed a mixed methods design combining surveys from 300 volunteers and interviews with 15 participants across three disaster categories. Empathy and collectivism emerged as significant predictors of altruistic intentions (R² = 0.225), while belief in a just world showed no effect. ANOVA results indicated consistent altruism across disaster types, pointing to strong cultural stability. Qualitative data reinforced these findings, highlighting the role of gotong royong, spirituality, and communal identity in sustaining volunteer engagement. This study contributes to the literature by challenging Western-centric models of prosocial behavior and demonstrating the importance of culturally grounded strategies such as involving community leaders and integrating traditional values in volunteer management. It advocates for cross-cultural disaster response frameworks that prioritize local knowledge and social cohesion.